2012
DOI: 10.1097/ccm.0b013e31826571f2
|View full text |Cite
|
Sign up to set email alerts
|

Variable compliance with clinical practice guidelines identified in a 1-day audit at 66 French adult intensive care units*

Abstract: At the bedside, clinical guidelines are fully applied in 24% of patients. Our study underlines the need to both improve the process of implementation and become cognizant of excessive proliferation of clinical guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 49 publications
2
51
0
5
Order By: Relevance
“…A survey conducted on-site at each ICU by personnel not belonging to the unit could reduce this potential bias. This type of study has been carried out in France on a different topic [28]. However, given the low incidence of brain death, this type of audit seems disproportionate.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A survey conducted on-site at each ICU by personnel not belonging to the unit could reduce this potential bias. This type of study has been carried out in France on a different topic [28]. However, given the low incidence of brain death, this type of audit seems disproportionate.…”
Section: Discussionmentioning
confidence: 98%
“…Twenty percent of other ICUs followed a protocol [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The combination of these two reasons was chosen by 35% of respondents.…”
Section: Availability Of Conϐirmatory Tests (%)mentioning
confidence: 99%
“…A 1-day audit of intensive care practice showed that a MAP goal was pre-fixed in only 70% of patients with septic shock [31]. In most patients, physicians seem to target a MAP of greater than 65 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…Others felt their pediatric early warning systems served the same purpose on the wards, and still others felt that introduction of the sepsis guideline implied that they were managing sepsis incorrectly beforehand. These reasons for skepticism are not unique to any single institution or any particular guideline and imply that crafting a resource-appropriate guideline is an important process but without attention to cultural issues, implementation and adoption are likely to be less than optimal (Figure 3[24]). Another area that has hindered adoption and sustainability is the failure to measure meaningful outcomes and share the information widely with team members.…”
Section: Reasons For Poor Adherencementioning
confidence: 99%